Grazing intensities and poultry litter fertilization levels on corn and black oat yield - Adami, Paulo Fernando; Pelissari, Adelino; Moraes, Anibal de; Modolo, Alcir José; Assmann, Tangriani Simione; Cassol, Luís César; Franchin, Marcia Fernanda (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to assess the effect of poultry litter fertilization levels on corn and black oat yield using different grazing intensities, poultry litter levels (mixture of manure and bedding material) and a chemical fertilization level. The experimental design was a randomized complete block in a split‑plot arrangement with four replicates. Black oat + ryegrass grazing intensities, characterized by different pasture sward management, with animal entrance at 25, 30 and 35‑cm heights and exit at 5.0, 10 and 15‑cm heights, were established at the main plots. After the grazing period, corn was grown at the subplots with four levels of poultry litter (0, 4,953, 9,907 and 14,860 kg ha‑1), aiming to supply 0, 100, 200 and 300 kg ha‑1 of nitrogen, and a treatment with chemical fertilizer, according to soil analysis. Grazing intensities had no effect on corn yield. Corn yield was 7,493, 8,458, 9,188, 10,247 and 11,028 kg ha‑1, respectively, for the treatments withoutand with 4,953, 9,907 and 14,860 kg ha‑1 of poultry litter, and the treatment with chemical fertilization. Poultry litter levels have a residual effect on the production of black oat grown in succession to corn.
Keywords: Avena strigosa; Zea mays; chemical fertilizer; organic fertilizer; residual effect; yield components.